Do Business Types Matter? A Comparative Analysis of Financial Management Quality among MSMEs in Makassar City - Muhaidir Ikram (PT Maju Malaqbi Makkarana, 2026)
This study aims to examine differences in financial management quality among Micro, Small, and Medium Enterprises (MSMEs) in Makassar City based on business type, namely trade, service, and processing industry. This research employed a quantitative comparative design involving 200 MSME actors, selected using a non-probability purposive sampling technique based on respondent eligibility and relevance to the research objectives. Financial management quality was measured using eight indicators: financial transaction recording, separation of personal and business finances, budgeting practice, periodic financial planning, cash flow monitoring, cost control, simple income statement preparation, and financial report-based decision-making. The data were analyzed using descriptive statistics, validity and reliability tests, homogeneity testing, One-Way Analysis of Variance, and Tukey HSD post hoc test. The findings show that financial management quality among MSMEs in Makassar City was generally categorized as good across all business types. Processing industry MSMEs obtained the highest average score, followed by service MSMEs and trade MSMEs. The strongest indicator was the separation of personal and business finances, while simple income statement preparation remained relatively weaker. The comparative test revealed that only cash flow monitoring differed significantly across business types, particularly between trade and processing industry MSMEs. These findings indicate that business type partially differentiates financial management quality, especially in cash flow monitoring. Therefore, MSME financial development programs should be adjusted to the operational characteristics of each business type.